Development of Guided Inquiry-Based Student Worksheets for Optimizing Mathematical Understanding Skills - Evaldus, Jenefer Delano; Sridana, Nyoman; Made Intan Kertiyani, Ni; Soepriyanto, Harry (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The application of teacher-centered learning in one of the high schools in Mataram City resulted in low mathematical understanding skills in students. This is because teachers only use textbooks as learning tools and rarely use student worksheets. The purpose of this study was to develop valid and effective guided inquiry-based student worksheets. The type of research used is research and development using the 4D model which is carried out to the development stage. Data collection techniques used interview guidelines, learner response questionnaires, and mathematical understanding ability tests. The data analysis technique consisted of validity analysis and effectiveness analysis. The results of data analysis showed that the learner worksheet product developed obtained a score of 4.30 by 1 device expert validator with very valid criteria, then received a score of 4.71 by 1 material expert validator with very valid criteria and obtained a score of 4.44 by 1 learning expert validator with very valid criteria. Furthermore, the guided inquiry-based student worksheet is an effective learning tool because the percentage of classical completeness reached 77.78% and the percentage of student response scores was 83% with very good criteria. So, it can be concluded that the development of guided inquiry-based student worksheets is valid and effective for optimizing students' mathematical understanding skills.